Psychosis, Telehealth, and COVID-19: Successes and Lessons Learned From the First Wave of the Pandemic. (16th October 2022) - Chaudhry, Serena; Weiss, Ashley; Dillon, Grinasha; O'Shea, Ariana; Hansel, Tonya Cross
Abstract: Objective: This brief report analyzes a first-episode psychosis (FEP) clinic's shift from in-person treatment to the provision of services through telemental health during the 2019 coronavirus disease (COVID-19) pandemic. The feasibility of using this technology was examined by assessing client engagement. Methods: The authors created and implemented procedures for the clinic's transition to telemental health. Once clients' consents were obtained, the Health Insurance Portability and Accountability Act (HIPAA) compliant platform was used to continue service provision. Results: Client engagement during this period improved compared to that of the same quarter in the previous year. Telemental health was also practical for providing groups and other supportive services to meet clients' needs. Conclusion: Telemental health is an effective approach to providing care at an FEP clinic during a pandemic. Successes and lessons learned from the first wave of the pandemic can be used to prevent an uptick in symptoms and sustain engagement for this vulnerable population during the anticipated second wave.